Local Data and Global Ideas. Citymaking in Times of Digital Transformation. - Bangratz, Martin; Förster, Agnes (RWTH Aachen University, 2021)
As every aspect of life is transformed by digital technology, new challenges and opportunities arise for the design and governance of urban areas. So-called citymakers, the actors involved in collaborative processes of urban development, are increasingly using technology and data to support their efforts. They join forces with technology experts in global, virtual networks to exchange ideas and solutions, and transcend the local scale. Despite justified criticism of digitalization in cities today, it is clear that data and technology are expediting citymaking processes; at the same time, said processes may also contribute to more equitable urban data and technology governance. The present research combines different views on the matter from a preliminary literature review with observations of digital citymaking processes in practice. The findings are structured into two modes of operation between virtual and physical space, and related to formal processes of urban development.
Keywords: Urban Governance; Stadtentwicklung; Digitalisierung; Kooperation; Urbanismus; Akteur; Transformation; Vernetzung; Partizipation; Citymaker; Lokale Demokratie; Empowerment; Stadtmachen